2022
DOI: 10.1038/s41598-022-06958-2
|View full text |Cite
|
Sign up to set email alerts
|

Urban–rural prostate cancer disparities in a regional state of Australia

Abstract: Men living in regional and remote areas experience disparities in prostate cancer (PrCa) diagnosis, clinical characteristics and treatment modalities. We sought to determine whether such disparities exist in PrCa patients from Tasmania; a regional state of Australia with the second-highest rate of diagnosis and where over a third of residents live in outer regional and remote areas. Our study included clinicopathological data from 1526 patients enrolled in the Prostate Cancer Outcomes Registry-Tasmania. Regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Multiple studies have demonstrated that rural patients are diagnosed with cancer at an older age and with more aggressive clinical characteristics. Overall, an advanced stage at diagnosis and restricted access to cancer treatment, including clinical trials, contribute to poorer prognoses [14,15]. Maganty et al discovered that rural residents were less likely to undergo PCa treatment than urban residents across all risk categories, including low-[adjusted odds ratio (aOR):0.77], intermediate-[aOR:0.71], and high-risk disease [aOR:0.680] [16].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that rural patients are diagnosed with cancer at an older age and with more aggressive clinical characteristics. Overall, an advanced stage at diagnosis and restricted access to cancer treatment, including clinical trials, contribute to poorer prognoses [14,15]. Maganty et al discovered that rural residents were less likely to undergo PCa treatment than urban residents across all risk categories, including low-[adjusted odds ratio (aOR):0.77], intermediate-[aOR:0.71], and high-risk disease [aOR:0.680] [16].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, there are considerable inequities reported between urban and rural dwelling survivors of cancer [39]. Although the incidence of cancer is typically higher in urban areas, those from more rural communities have an elevated risk of poor health outcomes, with higher levels of cancer-related morbidity and mortality consistently reported [40,41]. These findings may be attributed to the limited availability of clinical care and supportive care services in rural areas, the acknowledged transportation barriers, and the significantly higher financial burden (eg, increased transport costs and increased time away from employment) experienced by rural survivors of cancer.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Fonte: Datasus (2024).As desigualdades entre as Regiões Brasileiras podem ocorrer devido a desigualdade de acesso à saúde, social e econômica do Estado. Comunidades mais vulneráveis socioeconomicamente estão incluídas em um acesso mais escasso à hospitais especializados e com uma densidade de médicos por 1000 habitantes(Simbana-Rivera et al, 2023); em contraste, áreas socialmente mais favorecidas e urbanas têm mais facilidade de acesso(Evangelista et al, 2022) Foley et al (2022). observou que homens residentes em áreas remotas apresentam diferença no diagnóstico, nas características clínicas da doença e no tratamento.…”
unclassified